Communication repair in parole oral hearings: Comparing remote and in-person settings - Peplow, David (Journal of criminology, 2024)
The Parole Board (PB) for England and Wales is responsible for deciding whether prisoners are safe to be released into the community. Although the PB was using remote formats (teleconferencing and videoconferencing) to conduct hearings prior to 2020, the coronavirus (COVID-19) pandemic accelerated the wider application of remote hearings. Such changes in modality can have a significant impact on interactional practices, with participation in remote communication requiring a different set of skills from those normally involved in in-person interaction. We argue that this shift in modality is important because it risks impeding prisoners’ participation in hearings and may limit the legitimacy of a parole hearing decision when examined through the lens of procedural justice theory. In this article, we draw on a dataset of 30 recordings of in-person and remote oral hearings. We analyse sections in which prisoners are questioned by PB panel members to identify whether these interactions can be deemed to be as successful in remotely held hearings as compared with in-person hearings. To assess this, we compare instances of communication problems that occur in the datasets. Applying conversation analysis, we find that instances of repair work from participants are statistically more likely to be present in remote hearings when compared to in-person settings. Our analysis has implications for the operating model being used by the PB and knowledge around participation in remotely held justice contexts.